A novel laminin β gene BmLanB1-w regulates wing-specific cell adhesion in silkworm, Bombyx mori - Tong, Xiaoling (Sci Rep, 2015)
Laminins are important basement membrane (BM) components with crucial roles in development. The numbers of laminin isoforms in various organisms are determined by the composition of the different α, β, and γ chains, and their coding genes, which are variable across spieces. In insects, only two α, one β, and one γ chains have been identified thus far. Here, we isolated a novel laminin β gene, BmLanB1-w, by positional cloning of the mutant (crayfish, cf) with blistered wings in silkworm. Gene structure analysis showed that a 2 bp deletion of the BmLanB1-w gene in the cf mutant caused a frame-shift in the open reading frame (ORF) and generated a premature stop codon. Knockdown of the BmLanB1-w gene produced individuals exhibiting blistered wings, indicating that this laminin gene was required for cell adhesion during wing development. We also identified laminin homologs in different species and showed that two copies of β laminin likely originated in Lepidoptera during evolution. Furthermore, phylogenetic and gene expression analyses of silkworm laminin genes revealed that the BmLanB1-w gene is newly evolved, and is required for wing-specific cell adhesion. This is the first report showing the tissue specific distribution and functional differentiation of β laminin in insects.